Pengaruh Sekolah Pasar Modal terhadap Pengetahuan Investasi Saham Mahasiswa Manajemen Keuangan Syariah UIN Sayyid Ali Rahmatullah Tulungagung - Nurfikasari, Fariha; Dwi Warsitasari, Wahyu (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to see the difference before and after the implementation of the Capital Market School (SPM) on stock investment knowledge in Sharia Financial Management (MKS) study program students, Faculty of Economics and Islamic Business (FEBI) UIN Sayyid Ali Rahmatullah Tulungagung. The type of approach used in this research is a quantitative approach, while the type of research is quasi experimental (pseudo experimental research). The research design used is one group pre test-post test design, so that research data is obtained from SPM participants as respondents who are measured using a pre-test before the SPM is implemented, and a post-test after the SPM. The population used is MKS students who are SPM participants, with a total population of 129. While the sample used was 30 MKS students as SPM participants who met the criteria in sampling. The sampling technique is purposive sampling using predetermined sampling criteria. While the type of data source used is primary data, which is obtained from the pre-test and post-test of SPM participants. The variables used are SPM as the dependent variable, and stock investment knowledge as the independent variable. While the data collection technique used is the test method, all of which data is obtained from the results of measuring the investment knowledge of MKS students using measuring instruments in the form of pre-test and post-test. The results of hypothesis testing using paired sample t-test show that there is a significant difference in students' stock investment knowledge before and after the implementation of SPM.